The applicability of the Eclectic Paradigm to explain the FDI source from Taiwan to China market and the reason of wholly owned subsidiary favoured by Taiwanese MNEs in China - Hsieh, Pei Jung (2009)
Since 1980, the propelling power of international trade has been shifted to FDI. The capital flow has become more frequently and penetrative across national boundaries. Conventionally, the sources of FDI generally came from the United States, the United Kingdom, Germany and Japan. However, since 1990 China has been one of the most burgeoning economies and has become the largest FDI recipient among developing countries. And Taiwan was appeared as one of the primary sources of inward FDI in China. Therefore, the aim of this paper attempts to examine the applicability of the Eclectic Paradigm regarding to the FDI source from Taiwan to China and to explore the favoured entry mode of Taiwanese MNEs on the ground of transaction cost theory. The qualitative analysis was conducted in order to gain detailed apprehensions and in-depth analysis. This research involves four case studies of the Taiwanese manufacturing MNEs in the Chinese market; comprised of interview and documentary data collection approaches. The findings of this research reveal that the Taiwanese MNEs can be understood by configurations of the Eclectic Paradigm and the preference of wholly owned subsidiary entry mode adopted by Taiwanese MNEs would be result from their intangible ownership advantages in the view of transaction cost. To conclude, this research would be importance in examining the applicability of the Eclectic Paradigm as well as in ascertaining the reason of employing wholly owned subsidiary favoured by Taiwanese manufacturing MNEs.